Health Expenditure Comparisons: Low, Middle and High Income Countries - Hopkins, Sandra (Bentham Science Publishers, 2010)
Cross-sectional health expenditure data are used to compare health expenditure aggregates and the contributionof the public and private sectors in a selection of 31 low, middle and high income countries. The comparative dataillustrate the diversity of outcomes in terms of total health expenditure and its components even amongst countries with similar GDP per capita. Low and middle income countries on the whole, rely more heavily on private funding especially household out-of-pocket payments. Public funding is more prevalent for funding of curative care than for funding of pharmaceuticals in high, middle and low income countries. The results illustrate the usefulness of internationally comparable health expenditure data to undertake cross country comparisons. Such comparisons are crucial for contributing to evidence based policy.